Amphiphilic Janus carbon nanotube thick oil emulsifying viscosity reducer as well as preparation method and application thereof
Through the surface modification and modification of the amphiphilic Janus carbon nanotubes, nanofluids with high interfacial activity are formed, which solves the problem of limited viscosity reduction effect of heavy oil emulsification in the prior art, and achieves efficient recovery of heavy oil and reduces costs.
Patent Information
- Application Number
- CN202510301157.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-14
AI Technical Summary
The prior art has limited effect in reducing viscosity of heavy oil emulsification, which leads to the need to improve the recovery rate of heavy oil and is insufficient cost-efficiency.
An amphiphilic Janus carbon nanotubes are used as a heavy oil emulsification and viscosity reducing agent. Through the surface modification and modification of multi-wall carbon nanotubes, nanofluids with prominent Janus asymmetry, amphiphilicity and interfacial activity are formed, which is used to reduce oil-water interface tension and improve the recovery rate of heavy oil.
The viscosity reduction rate of heavy oil reaches 99.47%, the recovery rate is improved by more than 25%, and it is low-cost and efficient, and is suitable for large-scale applications on site.
Smart Images

Figure CN119799301A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heavy oil emulsification and viscosity reduction, in particular to an amphiphilic Janus carbon nanotube heavy oil emulsification and viscosity reduction agent and a preparation method and application thereof. Background Art
[0002] Crude oil with high viscosity and high specific gravity is called heavy oil. According to statistics, heavy oil reservoirs account for 35% of the world's total oil reservoir content. Due to the increasing world energy demand, a large number of conventional oil reservoirs have entered the depletion stage. Heavy oil reservoirs still have great potential for exploitation due to their difficulty and high cost of exploitation, but how to exploit heavy oil at low cost and high efficiency is a difficult problem that needs to be solved.
[0003] Due to its high viscosity, the natural interfacial active components such as colloid asphaltene contained in heavy oil can cause self-emulsification between heavy oil and water, forming The emulsion further increases the viscosity of the heavy oil, causing the heavy oil to have extremely low flow properties or even no flow properties.
[0004] Heavy oil reservoirs' enhanced oil recovery technologies usually include heavy oil thermal recovery, heavy oil chemical flooding, heavy oil in-situ catalytic upgrading, and gas injection recovery. Heavy oil chemical flooding has advantages over other recovery methods. Compared with thermal recovery, it has low energy consumption, less damage to the formation, and a wide range of applications; compared with in-situ catalytic upgrading, it has low cost, simple process, and low risk; and compared with gas injection recovery, it has high oil recovery efficiency, strong adaptability, and less impact on the environment.
[0005] In the prior art, the invention patent with publication number CN115806812A discloses a preparation method and application of a heavy oil emulsified viscosity reducer, and a surfactant is prepared by adjusting the hydrophilic-lipophilic balance, which can form an oil-in-water emulsion with heavy oil to reduce the viscosity of heavy oil. The heavy oil emulsified viscosity reducer contains anionic sulfonate surfactant, nonionic surfactant and water, and the anionic sulfonate surfactant is an anionic sulfonate surfactant with a multi-branched structure based on the hydrophobic tail chain of the superimposed olefin, and the emulsified viscosity reduction rate exceeds 90%. Therefore, reducing the viscosity of heavy oil is of great significance to improving the recovery rate, but its recovery rate still needs to be improved, and how to further exploit heavy oil at low cost and high efficiency still needs to be solved. Summary of the invention
[0006] The purpose of the present invention is to provide an amphiphilic Janus carbon nanotube heavy oil emulsifying viscosity reducer and a preparation method and application thereof, with a viscosity reduction rate of 99.47%, excellent wetting reversal and interfacial tension reduction capabilities, and an increased oil recovery rate of more than 25%, with a significant effect of increased oil recovery.
[0007] To achieve the above object, the present invention provides a method for preparing an amphiphilic Janus carbon nanotube heavy oil emulsifying viscosity reducer, comprising the following steps: S1, adding multi-walled carbon nanotubes to a strong acid solution according to a certain proportion, heating and stirring, and then filtering, washing and drying to obtain activated carbon nanotubes with surface modified with hydroxyl groups; S2, adding the activated carbon nanotubes obtained in S1 to the first solvent and then adding molten paraffin, heating and stirring, and then filtering, washing and drying to obtain paraffin microspheres wrapped by the activated carbon nanotubes; S3, adding the paraffin microspheres obtained in S2 to the second solvent, heating and stirring under the action of the first catalyst, and then filtering and washing to obtain carbon nanotube paraffin microspheres asymmetrically modified with vinyltrimethylsilane; S4. Add the carbon nanotube paraffin microspheres obtained in S3 to the third solvent, heat, stir, reflux and react with the first modifier under the action of the second catalyst and N2, dissolve, wash and filter, then add to the fourth solvent, react with the second modifier under the action of the third catalyst, heat, stir, wash and filter to obtain reduced viscosity Janus carbon nanotubes.
[0008] Preferably, in S1, the mass ratio of the multi-walled carbon nanotubes to the strong acid solution is 1g:60-80ml; the strong acid solution is a mixed solution of 98% sulfuric acid and 65% nitric acid, and the volume ratio of sulfuric acid to nitric acid is 3:1.
[0009] Preferably, S1 is specifically: The multi-walled carbon nanotubes are added to a strong acid solution, stirred at 85-100°C and 12000-13000 rpm / min for 4-5 hours, then washed with ethanol until the pH of the solution is neutral, filtered and dried to obtain activated carbon nanotubes with surface modified hydroxyl groups.
[0010] Preferably, in S2, the mass ratio of the activated carbon nanotubes, the first solvent and the paraffin is 1-2 g:100 ml:6-10 g; The first solvent is a mixed solution of 0.02% hexadecyltrimethylammonium bromide, 6.7% ethanol and water.
[0011] Preferably, S2 is specifically: The activated carbon nanotubes obtained in S1 are added to the first solvent and then molten paraffin, stirred at 75-80°C and 12000-13000 rpm / min for 30-35 min, then washed with ethanol, filtered and dried to obtain paraffin microspheres wrapped with activated carbon nanotubes.
[0012] Preferably, in S3, the mass ratio of the paraffin microspheres, the second solvent and the first catalyst is 1-2 g:100 ml:0.6-1.0 ml; The second solvent is a mixed solution of vinyltrimethoxysilane, ethanol and water, and the mass ratio of the vinyltrimethoxysilane, the ethanol and the water is 6-8:96:4; The first catalyst is glacial acetic acid.
[0013] Preferably, in S4, the amount of the carbon nanotube paraffin microspheres added is 1.8% to 2% of the amount of the third solvent added; The third solvent is deionized water; The second catalyst is one or both of ammonium persulfate and NaOH, and the amount of the second catalyst added is 0.01% to 0.03% of the third solvent; The first modifier is a mixture of maleic acid and sodium vinyl sulfonate, the mass ratio of maleic acid to sodium vinyl sulfonate is 1-1.5, and the amount of the first modifier added is 1.8%-2% of the amount of the third solvent added; The fourth solvent is one of toluene, petroleum ether or n-octane; The third catalyst is NaOH, and the addition amount of the third catalyst is 0.01% to 0.02% of the fourth solvent; The second modifier is 1-bromooctadecane, and the added amount of the second modifier is 2% to 3% of the fourth solvent.
[0014] Preferably, S4 is specifically: The carbon nanotube paraffin microspheres obtained in S3 are added to the third solvent, and then the second catalyst is added, and N2 is introduced for 25 to 30 minutes, and stirred and refluxed at 45 to 50°C to react with the first modifier for 4 to 5 hours, and one of n-heptane, petroleum ether or acetone is added for dissolution treatment, and then washed with anhydrous ethanol, filtered and added to the fourth solvent, and reacted with the second modifier for 8 to 10 hours at 60 to 65°C and 400 to 600 r / min under the action of the third catalyst, washed and filtered to obtain reduced viscosity Janus carbon nanotubes.
[0015] To achieve the above purpose, the present invention also provides an amphiphilic Janus carbon nanotube heavy oil emulsifier and viscosity reducer, which comprises uniformly mixing sodium polyoxyethylene fatty alcohol ether sulfate, cocamidopropyl betaine, water and the viscosity reducing Janus carbon nanotubes to obtain the amphiphilic Janus carbon nanotube heavy oil emulsifier and viscosity reducer.
[0016] To achieve the above object, the present invention also provides an amphiphilic Janus carbon nanotube heavy oil emulsification viscosity reducer, and its application in heavy oil emulsification viscosity reduction to enhance oil recovery.
[0017] Therefore, the present invention adopts the above-mentioned amphiphilic Janus carbon nanotube heavy oil emulsification viscosity reducer and its preparation method and application, and the beneficial effects are as follows: (1) Compared with the prior art, the preparation method of the present invention uses multi-walled carbon nanotubes as the base material, increases the coverage rate of paraffin microspheres by adding hexadecyltrimethylammonium bromide and optimizes the modification sequence and conditions, introduces hydrophilic long chains into carbon nanotubes through emulsion polymerization and Williamson reaction, and has more prominent Janus asymmetry, amphiphilicity and interfacial activity. Nanofluids are formed by compounding to reduce the oil-water interfacial tension, that is, reduce the heavy oil reservoir and stabilize the emulsion, thereby improving the heavy oil recovery rate.
[0018] (2) Compared with the 90% viscosity reduction rate of the prior art, the viscosity reduction rate of the emulsified viscosity reducer of the present invention reaches 99.47%, which is higher than most emulsified viscosity reducers. The nanofluid can not only reduce the oil-water interfacial tension, but also increase the recovery rate by more than 25%, which has a significant effect on improving the recovery rate; (3) Compared with conventional viscosity reducers, the present invention has the characteristics of low cost and high efficiency, can reduce the amount of surfactant added, and can be widely used on site.
[0019] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the synthesis of an amphiphilic Janus carbon nanotube heavy oil emulsifying viscosity reducer and its preparation method and application example of the present invention; Figure 2 This is an FT-IR characteristic curve diagram of an amphiphilic Janus carbon nanotube heavy oil emulsifying viscosity reducer and its preparation method and application example of the present invention; Figure 3 This is an experimental flow chart of improving oil recovery of an amphiphilic Janus carbon nanotube heavy oil emulsifying viscosity reducer and its preparation method and application example of the present invention; Figure 4 This is a diagram showing the results of an experiment to improve oil recovery of an amphiphilic Janus carbon nanotube heavy oil emulsifying viscosity reducer and its preparation method and application example of the present invention. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0022] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0023] Example 1 like Figure 1 As shown, a viscosity reducing (amphiphilic) Janus carbon nanotube, the structural formula of the hydrophilic group is as follows: .
[0024] The preparation method is as follows: (1) Prepare 80 ml of a strong acid solution by mixing 98% concentrated sulfuric acid and 65% concentrated nitric acid in a volume ratio of 3:1. Add 1 g of multi-walled carbon nanotubes to the strong acid solution, heat and stir for 4 h, wash until the carbon nanotube solution is neutral, and filter and dry to obtain activated carbon nanotubes with surface modified hydroxyl groups.
[0025] (2) Take 1 g of activated carbon nanotubes and add them into 100 ml of 6.7% ethanol solution. Ultrasonic disperse them for 30 min, then add 0.02 g of hexadecyltrimethylammonium bromide and 6 g of molten paraffin. Stir at 75 °C and 12000 rpm / min for 30 min to obtain a paraffin microsphere solution wrapped with activated carbon nanotubes.
[0026] (3) Filtration and washing to obtain paraffin microspheres wrapped by activated carbon nanotubes.
[0027] (4) Place the paraffin microspheres in a beaker, add 96 mL of ethanol and 4 mL of deionized water in sequence, stir evenly, and disperse by ultrasonication for 30 min to obtain a paraffin microsphere dispersion.
[0028] (5) Add 6% vinyltrimethoxysilane solution into a round-bottom flask, then add glacial acetic acid to adjust the pH to weak acidity, add paraffin microsphere dispersion and mix well, then heat with stirring and reflux at 75 °C for 4 h.
[0029] (6) Filter and wash to obtain carbon nanotube paraffin microspheres asymmetrically modified with vinyltrimethylsilane.
[0030] (7) Prepare 100 ml of 2% paraffin microsphere dispersion with the obtained paraffin microspheres. Add 2 g of maleic acid and sodium vinyl sulfonate in a mass ratio of 1:1, adjust the pH value to (weakly alkaline) 7-8, and after ultrasonic dispersion for 30 min, add it to a three-necked flask, pass N2 for 30 min, then add 0.03 g of ammonium persulfate, and heat at 50°C with stirring and reflux for 4 h.
[0031] (8) After filtration, the paraffin microspheres are repeatedly washed with n-heptane, filtered, washed, and dried to obtain asymmetric hydrophilic long-chain modified activated carbon nanotubes.
[0032] (9) Take 1 g of the activated carbon nanotubes obtained in step (8) above and add it to 50 ml of petroleum ether for ultrasonic dispersion for 30 min. Then add 1 g of 1-bromooctadecane and a small amount of NaOH and react at 60 °C and 400 rpm / min for 8 h.
[0033] (10) Filter, wash and dry to obtain amphiphilic Janus carbon nanotubes.
[0034] Experimental Testing (1) FT-IR test The functional group composition of multi-walled carbon nanotubes and the amphiphilic Janus carbon nanotubes prepared in Example 1 was analyzed by FT-IR. The results are as follows: Figure 2 shown.
[0035] Depend on Figure 2 It can be seen that 3418cm -1 and 1704cm -1 The peaks at 2920cm are the stretching vibration characteristic peaks of hydroxyl and carbonyl groups; -1 and 2850cm -1 、1400cm -1 They are the characteristic peaks of antisymmetric stretching vibration, symmetric stretching vibration, and in-plane bending vibration of CH in methylene; 1120cm -1 It is the characteristic peak of SO stretching vibration; 1032cm -1 It is the characteristic peak of Si-O stretching vibration; 749cm -1 It is the characteristic peak of CS stretching vibration. 1032cm -1 The peak at 3418cm represents the successful grafting of vinyltrimethoxysilane on the surface of carbon nanotubes; -1 and 1704cm -1 The peak at 1120cm indicates that maleic acid has been successfully grafted. At the same time, it can be found that compared with the amphiphilic modified Janus carbon nanotubes before modification, there is one more carbonyl stretching vibration peak, which further verifies the successful grafting of maleic acid; 1120cm -1 and 749cm -1 The two peaks represent sulfonic acid groups, which can indicate that sodium vinyl sulfonate has been successfully introduced into the surface of carbon nanotubes. By comparing the amphiphilic Janus carbon nanotubes before and after modification, it can be found that there are three more peaks at 2920cm -1 and 2850cm -1 、1400cm -1 , which can prove that the alkyl long chain is successfully introduced into the surface of carbon nanotubes. In summary, the amphiphilic Janus carbon nanotubes are successfully synthesized.
[0036] (2) Enhanced oil recovery test The amphiphilic Janus carbon nanotubes thick oil emulsifying and viscosity reducing agent was prepared by selecting 0.08% sodium fatty alcohol polyoxyethylene ether sulfate, 0.02% cocamidopropyl betaine, 0.02% amphiphilic Janus carbon nanotubes prepared in Example 1, and the balance being water.
[0037] The core displacement experiment was conducted to measure the recovery efficiency of the amphiphilic Janus carbon nanotube heavy oil emulsifier. The core with a water permeability of 1500 mD was selected for the core displacement experiment. The experimental process is as follows: Figure 3 As shown in the figure, the specific steps are as follows: first, vacuum the core and saturate it with simulated formation water. Then, at 65°C, use crude oil to saturate the water-saturated core at a rate of 0.1 ml / min until no water comes out of the end of the core holder. Then, close the valves at the front and rear ends of the core holder and place it in a 65°C oven for aging for 24 hours. Figure 3 Connect the pipeline, then inject simulated formation water at a rate of 0.5 ml / min until the water content reaches 98% and stop water injection, then inject 0.3 PV amphiphilic Janus carbon nanotube heavy oil emulsifier (nanofluid) at a rate of 0.5 ml / min. Then inject water at a flow rate of 0.5 ml / min until the water content at the outlet of the core holder reaches 98% and stop injection.
[0038] The flooding effect of the amphiphilic Janus carbon nanotube heavy oil emulsifier was measured. During the whole process, the injection pressure, water content, and cumulative recovery rate were recorded every 0.05 PV injection volume, and the water content, recovery rate, and injection pressure curves were plotted. The water content calculation formula is shown in formula (1), and the recovery rate calculation formula is shown in formula (2).
[0039] (1) In the formula, is the moisture content; is the water content in the produced fluid, ml; is the total volume of produced fluid, ml.
[0040] (2) In the formula, E is the recovery factor; is the cumulative volume of produced oil, ml; is the volume of oil in the rock pores, ml.
[0041] The results of the enhanced oil recovery experiment are as follows Figure 4As shown in the figure, when the primary water flooding begins, due to the oil-water two-phase flow, the core water saturation is low, the relative permeability of the water phase is low, and the displacement resistance is large, which is manifested as a sharp rise in pressure. However, with the formation of the water flooding dominant channel, the pressure gradually decreases and tends to be stable. In this stage, the water content and recovery rate rise sharply until the high water content stage is reached, and the recovery rate basically does not change. After the primary water flooding is completed, with the injection of the amphiphilic Janus carbon nanotube heavy oil emulsified viscosity reducer, the recovery degree has increased slightly. This may be because the amphiphilic Janus carbon nanotube heavy oil emulsified viscosity reducer contacts the rock, causing the rock to reverse its wettability, peeling off the oil film on the rock surface, and at the same time, under the action of shear force, it forms a water-in-oil emulsion with the residual oil to carry it out. After the secondary water flooding started, the crude oil recovery rate gradually increased and tended to be stable. At this time, the water content curve showed a "funnel" shape, and the pressure fluctuated significantly. This may be because the injection of the amphiphilic Janus carbon nanotube heavy oil emulsified viscosity reducer caused the subsequent water flooding to expand the swept volume, and due to the excellent interfacial tension reduction performance and emulsification and viscosity reduction performance of the amphiphilic Janus carbon nanotube heavy oil emulsified viscosity reducer, it formed an emulsion with the residual oil. When the emulsion passed through the small pores, the water flooding pressure increased due to the Jamin effect. However, with the continuous action of the shear force, the emulsion particle size gradually decreased and passed through the small pores, thus showing a continuous decrease in the injection pressure and a continuous increase in the recovery rate. The recovery rate was improved by 26.16%, and the amphiphilic Janus carbon nanotube heavy oil emulsified viscosity reducer had excellent recovery capacity.
[0042] Therefore, the present invention adopts the above-mentioned amphiphilic Janus carbon nanotube heavy oil emulsification viscosity reducer and its preparation method and application, with a viscosity reduction rate of 99.47%, excellent wetting reversal and interfacial tension reduction capabilities, and an increase in recovery rate of more than 25%, with a significant effect in improving recovery rate.
[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an amphiphilic Janus carbon nanotube heavy oil emulsifying and viscosity reducing agent, characterized in that: The following steps are involved: S1, adding multi-walled carbon nanotubes to a strong acid solution according to a certain proportion, heating and stirring, and then filtering, washing and drying to obtain activated carbon nanotubes with surface modified with hydroxyl groups; S2, adding the activated carbon nanotubes obtained in S1 to the first solvent and then adding molten paraffin, heating and stirring, and then filtering, washing and drying to obtain paraffin microspheres wrapped by the activated carbon nanotubes; S3, adding the paraffin microspheres obtained in S2 to the second solvent, heating and stirring under the action of the first catalyst, and then filtering and washing to obtain carbon nanotube paraffin microspheres asymmetrically modified with vinyltrimethylsilane; S4. Add the carbon nanotube paraffin microspheres obtained in S3 to the third solvent, heat, stir, reflux and react with the first modifier under the action of the second catalyst and N2, dissolve, wash and filter, then add to the fourth solvent, react with the second modifier under the action of the third catalyst, heat, stir, wash and filter to obtain reduced viscosity Janus carbon nanotubes.
2. The method for preparing an amphiphilic Janus carbon nanotube heavy oil emulsifying and viscosity reducing agent according to claim 1, characterized in that: In S1, the mass ratio of the multi-walled carbon nanotubes to the strong acid solution is 1g:60-80ml; the strong acid solution is a mixed solution of 98% sulfuric acid and 65% nitric acid, and the volume ratio of sulfuric acid to nitric acid is 3:
1.
3. The method for preparing an amphiphilic Janus carbon nanotube heavy oil emulsifying and viscosity reducing agent according to claim 1, characterized in that: S1 is specifically: The multi-walled carbon nanotubes are added to a strong acid solution, stirred at 85-100°C and 12000-13000 rpm / min for 3-4 hours, then washed with ethanol until the pH of the solution is neutral, filtered and dried to obtain activated carbon nanotubes with surface modified hydroxyl groups.
4. The method for preparing an amphiphilic Janus carbon nanotube heavy oil emulsifying and viscosity reducing agent according to claim 1, characterized in that: In S2, the mass ratio of the activated carbon nanotubes, the first solvent and the paraffin is 1-2 g:100 ml:6-10 g; The first solvent is a mixed solution of 0.02% hexadecyltrimethylammonium bromide, 6.7% ethanol and water.
5. The method for preparing an amphiphilic Janus carbon nanotube heavy oil emulsifying and viscosity reducing agent according to claim 1, characterized in that: S2 is specifically: The activated carbon nanotubes obtained in S1 are added to the first solvent and then molten paraffin, stirred at 75-80°C and 12000-13000 rpm / min for 30-35 min, then washed with ethanol, filtered and dried to obtain paraffin microspheres wrapped with activated carbon nanotubes.
6. The method for preparing an amphiphilic Janus carbon nanotube heavy oil emulsifying and viscosity reducing agent according to claim 1, characterized in that: In S3, the mass ratio of the paraffin microspheres, the second solvent and the first catalyst is 1-2 g:100 ml:0.6-1.0 ml; The second solvent is a mixed solution of vinyltrimethoxysilane, ethanol and water, and the mass ratio of the vinyltrimethoxysilane, the ethanol and the water is 6-8:96:4; The first catalyst is glacial acetic acid.
7. The method for preparing an amphiphilic Janus carbon nanotube heavy oil emulsifying and viscosity reducing agent according to claim 1, characterized in that: In S4, the amount of the carbon nanotube paraffin microspheres added is 1.8% to 2% of the amount of the third solvent added; The third solvent is deionized water; The second catalyst is one or both of ammonium persulfate and NaOH, and the amount of the second catalyst added is 0.01% to 0.03% of the third solvent; The first modifier is a mixture of maleic acid and sodium vinyl sulfonate, the mass ratio of maleic acid to sodium vinyl sulfonate is 1-1.5, and the amount of the first modifier added is 1.8%-2% of the amount of the third solvent added; The fourth solvent is one of toluene, petroleum ether or n-octane; The third catalyst is NaOH, and the addition amount of the third catalyst is 0.01% to 0.02% of the fourth solvent; The second modifier is 1-bromooctadecane, and the added amount of the second modifier is 2% to 3% of the fourth solvent.
8. The method for preparing an amphiphilic Janus carbon nanotube heavy oil emulsifying and viscosity reducing agent according to claim 1, characterized in that: S4 is specifically: The carbon nanotube paraffin microspheres obtained in S3 are added to the third solvent, and then the second catalyst is added, and N2 is introduced for 25 to 30 minutes, and stirred and refluxed at 45 to 50°C to react with the first modifier for 4 to 5 hours, and one of n-heptane, petroleum ether or acetone is added for dissolution treatment, and then washed with anhydrous ethanol, filtered and added to the fourth solvent, and reacted with the second modifier for 8 to 10 hours at 60 to 65°C and 400 to 600 r / min under the action of the third catalyst, washed and filtered to obtain reduced viscosity Janus carbon nanotubes.
9. An amphiphilic Janus carbon nanotube heavy oil emulsifying and viscosity reducing agent prepared by the preparation method of the amphiphilic Janus carbon nanotube heavy oil emulsifying and viscosity reducing agent according to any one of claims 1 to 8, characterized in that: The sodium polyoxyethylene fatty alcohol ether sulfate, cocamidopropyl betaine, water and the viscosity reducing Janus carbon nanotubes are uniformly mixed to obtain an amphiphilic Janus carbon nanotube heavy oil emulsifying viscosity reducing agent.
10. Use of the amphiphilic Janus carbon nanotube heavy oil emulsification and viscosity reduction agent as claimed in claim 9 in heavy oil emulsification and viscosity reduction to enhance oil recovery.
Citation Information
Patent Citations
Thickened oil emulsifying viscosity reducer as well as preparation method and application thereof
CN115806812A
Downhole delivery systems comprising epoxy ester polymers as support material
CA3011757A1
Amphiphilic Janus nano particle and preparation method and application thereof
CN111303853A
Phase change microcapsule based on polymer shell layer and manufacturing method thereof
CN111774017A
Janus type nano graphene oxide, thick oil viscosity reducer and preparation method of Janus type nano graphene oxide and thick oil viscosity reducer
CN115724761A
Cited By
Amphiphilic Janus tungsten disulfide nano emulsifying tackifier as well as preparation method and application thereof
CN121628604A
Amphiphilic Janus tungsten disulfide nano-emulsifying tackifier, and preparation method and application thereof
CN121628604B